Innovative technologies in growing and storing agricultural crops - Olkhovskyi, A. (Scientific Progress & Innovations, 2025)
The study presents a comprehensive analysis of modern innovative technologies used in the cultivation and storage of agricultural crops, with particular attention to the development of precision agriculture, digitalization, and biotechnological advances. The aim of the article is to characterize the main technological solutions that contribute to improving the efficiency, sustainability, and adaptability of agro-industrial systems under current global challenges. The methodology is based on the synthesis of recent scientific studies, sectoral analytics, and practical cases of technology implementation in Ukraine and internationally. The core findings indicate that precision agriculture technologies – such as variable rate application, remote field monitoring, automated equipment control, and satellite-based agroanalytics – enable farmers to optimize input use and reduce environmental pressure while increasing productivity. In parallel, the development of sensor systems and the Internet of Things significantly expands the possibilities of continuous real-time monitoring and automation across all stages of crop production. Internet of Things integration with farm management platforms also facilitates digital transformation at the enterprise level. The article also highlights the role of gene-editing tools, particularly CRISPR-Cas9, in developing stress-resistant and high-yielding crop varieties, which are essential for adapting to climate change. Furthermore, the research emphasizes the growing relevance of automated smart storage systems in Ukraine, which improve grain preservation efficiency, minimize post-harvest losses, and enhance logistical operations through microclimate control and digital interfaces. The article concludes that the integration of advanced agrotechnologies in Ukraine has great potential, despite existing challenges such as wartime disruption and limited investment. Practical implementation depends on the expansion of digital infrastructure, financial and educational support, and strengthening partnerships between agribusinesses and technology developers. The results confirm the strategic importance of innovations for building a resilient and competitive agricultural sector aligned with principles of sustainable development. Practical implementation depends on the expansion of digital infrastructure, financial and educational support, and strengthening partnerships between agribusinesses and technology developers. These findings may serve as a valuable reference for policy-makers, researchers, and practitioners seeking to modernize agricultural production and ensure long-term food security.